3-aryl-5-furylpyrazolines and their biological activities - Cetin, A; Cansiz, A; Digrak, M (Wiley, 2003)
Aryl-furyl substituted pyrazolines 2a-c and 4a-c were prepared by the reaction of alpha,beta-unsaturated carbonyl compounds with hydrazine or phenyl hydrazine. N-chloroacetyl derivatives 3a-c were obtained by the N-acetylation of 2a-c. The antibacterial activities of synthesized pyrazolines were examined by employing the disk-diffusion technique. All synthesized compounds showed antibacterial effects in 1200 mug concentration. (C) 2003 Wiley Periodicals, Inc.